Nanoscale real-time detection of quantum vortices at millikelvin temperatures - A. Guthrie (Nature Portfolio, 2021)
Previous work has shown the detection of quantum turbulence with mechanical resonators but with limited spatial and temporal resolution. Here, the authors demonstrate real-time detection of single quantum vortices in superfluid 4He with millisecond and micron resolution at temperatures of 10 millikelvin.